Checklist of angiosperm flora of Kuno National Park – a site for cheetah reintroduction in India - Verma, Ashutosh Kumar; Lakshmanudu, Bayyavarapu (Biodiversity: Research and Conservation, 2025)
The presented checklist provides up-to-date information on the angiosperm diversity of Kuno National Park. A total of 359 angiosperm species of 260 genera and 72 families were recorded during our study. Dicotyledons are represented by 63 families, 219 genera, and 299 species while monocotyledons by 9 families, 41 genera and 60 species. Information on the family, plant habits, phenology, collection numbers, and IUCN status of the documented species are also given.